Implementation of Ta'widh (Compensation) for Default Customers at KPR Platinum iB in the Perspective of Fatwa DSN-MUI No.129 / DSN-MUI / VII / 2019 at Bank BTN KCPS Karawaci - Abdul Rachman; Fikriana Aini (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
Purpose - This study aims to determine the implementation of ta'widh (compensation) for default customers on KPR Platinum iB in the perspective of Fatwa DSN-MUI No.129 / DSN-MUI / VII / 2019.Method - This study uses a qualitative analysis method with data collection techniques through observation, in-depth interviews and documentation. Purposive sampling technique is used by selecting sources who are considered the most knowledgeable related to the research topic.Result - The results of this study indicate that the implementation of ta'widh for default customers on the KPR Platinum iB is in accordance with the DSN-MUI Fatwa No.129 / DSN-MUI / VII / 2019. But in practice, there are several notes. The implementation of ta'widh and ta'zir at Bank BTN KCPS Karawaci is different. Ta'widh is charged to customers who experience delays in paying their obligations for more than 180 days and the ta'widh funds obtained will be recorded as Bank revenue. Ta'zir will be charged to customers who do not pay installments according to the due date and the ta'zir funds obtained will be recorded as non-halal income.Implication - This research can be used as a reference in measuring the conformity between the DNS-MUI Fatwa No. 129 / DSN-MUI / VII / 2019 with its implementation in the practice of financing in Islamic banks.Originality - This research focuses on analyzingimplementation of ta'widh (compensation) for default customers on KPR Platinum iB in the perspective of Fatwa DSN-MUI No.129 / DSN-MUI / VII / 2019..